The Effect of Voluntary and Electrically Stimulated Quadriceps Muscle Fatigue on Postural Control - Mostafa Sirousi; Mohammad Akbari; Zahra Teymuri; Asghar Akbari (Physical Treatments, 2018)
Purpose: The present study aimed to investigate the effect of voluntary and electrically stimulated quadriceps muscle fatigue on postural control. Methods: Sixteen healthy young males participated in this quasi-experimental study. All subjects performed two fatiguing exercises with equal intensity of isometric maximal voluntary contraction: Voluntary (VOL) and Electrical Stimulation (ES). The Centre of Pressure (CoP) displacement in the VOL and ES exercises were measured before and after conducting each protocol. The CoP displacement variables were analyzed by repeated measures ANOVA in SPSS. The Newman-Keuls post hoc test was used to determine the mean score differences. Results: The VOL and ES fatiguing exercises had significant effects on mean scores of sway area, mean velocity, anteroposterior, and mediolateral displacements. There was a significant difference between VOL and ES fatigue on postural control (P<0.05). Conclusion: The VOL fatiguing exercise impaired postural control more significantly than the ES fatiguing exercise. The disturbance of postural control in quadriceps muscle fatigue is related to the nature of the muscle contractions rather than the magnitude of strength loss.